The influence of energetic particle precipitation on Antarctic stratospheric chlorine and ozone over the 20th century - Maliniemi, Ville Aleksi; Arsenovic, Pavle; Seppälä, Annika; Tyssøy, Hilde Nesse (Atmospheric Chemistry and Physics, 2022)
Chlorofluorocarbon (CFC) emissions in the latter part of the 20th century reduced stratospheric ozone abundance substantially, especially in the Antarctic region. Simultaneously, polar stratospheric ozone is also destroyed catalytically by nitrogen oxides (NOx = NO + NO2) descending from the mesosphere and the lower thermosphere during winter. These are produced by energetic particle precipitation (EPP) linked to solar activity and space weather. Active chlorine (ClOx = Cl + ClO) can also react mutually with EPP-produced NOx or hydrogen oxides (HOx ) and transform both reactive agents into reservoir gases, chlorine nitrate or hydrogen chloride, which buffer ozone destruction by all these agents. We study the interaction between EPP-produced NOx , ClO and ozone over the 20th century by using free-running climate simulations of the chemistry–climate model SOCOL3-MPIOM. A substantial increase of NOx descending to the polar stratosphere is found during winter, which causes ozone depletion in the upper and mid-stratosphere. However, in the Antarctic mid-stratosphere, the EPP-induced ozone depletion became less efficient after the 1960s, especially during springtime. Simultaneously, a significant decrease in stratospheric ClO and an increase in hydrogen chloride – and partly chlorine nitrate between 10–30 hPa – can be ascribed to EPP forcing. Hence, the interaction between EPP-produced NOx /HOx and ClO likely suppressed the ozone depletion, due to both EPP and ClO at these altitudes. Furthermore, at the end of the century, a significant ClO increase and ozone decrease were obtained at 100 hPa altitude during winter and spring. This lower stratosphere response shows that EPP can influence the activation of chlorine from reservoir gases on polar stratospheric clouds, thus modulating chemical processes important for ozone hole formation. Our results show that EPP has been a significant modulator of reactive chlorine in the Antarctic stratosphere during the CFC era. With the implementation of the Montreal Protocol, ...